2016
DOI: 10.1002/ajmg.a.37645
|View full text |Cite
|
Sign up to set email alerts
|

Novel de novo mutations in ZBTB20 in Primrose syndrome with congenital hypothyroidism

Abstract: The cardinal features of Primrose syndrome (MIM 259050) are dysmorphic facial features, macrocephaly, and intellectual disability, as well as large body size, height and weight, and calcified pinnae. A variety of neurological signs and symptoms have been reported including hearing loss, autism, behavioral abormalities, hypotonia, cerebral calcifications, and hypoplasia of the corpus callosum. Recently, heterozygous de novo missense mutations in ZBTB20, coding for a zing finger protein, have been identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 12 publications
2
30
0
Order By: Relevance
“…Zbtb20 is a member of the BTB/POZ family of transcriptional repressors and functions primarily as a transcriptional repressor ( Xie et al , 2008); it is important for hippocampal development and function, the site of greatest Aβ deposition in aging J20 animals ( Mucke et al , 2000). Moreover, missense mutations in this gene are associated with Primrose syndrome, a cause of intellectual disability with autism ( Cordeddu et al , 2014; Mattioli et al , 2016). Additionally, haploinsufficiency of the gene has been suggested as an important factor in del3q13.31 syndrome, a cause of developmental delay and intellectual disability ( Rasmussen et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Zbtb20 is a member of the BTB/POZ family of transcriptional repressors and functions primarily as a transcriptional repressor ( Xie et al , 2008); it is important for hippocampal development and function, the site of greatest Aβ deposition in aging J20 animals ( Mucke et al , 2000). Moreover, missense mutations in this gene are associated with Primrose syndrome, a cause of intellectual disability with autism ( Cordeddu et al , 2014; Mattioli et al , 2016). Additionally, haploinsufficiency of the gene has been suggested as an important factor in del3q13.31 syndrome, a cause of developmental delay and intellectual disability ( Rasmussen et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, the missense variants in the YY1 gene that cause intellectual disability, also appear to cluster in the zinc finger domains, with different variants affecting the identical amino acid residue (Gabriele et al., ). Mutational clustering in the ZNF region is described for ZBTB20 (OMIM# 606025) as well, where de novo variants in the C2H2 ZNF domain of this protein lead to a hypothyroidism phenotype (Mattioli et al., ). In ZBTB42 (OMIM# 613915), a p.Arg>His in one of its C2H2 ZNF domains causes a lethal congenital contracture syndrome (Patel et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A ZBTB20 disruption due to a de novo balanced translocation has also been identified in a patient with similar clinical features (Rasmussen et al, ). Finally, in 2014, de novo mutations in ZBTB20 were identified in patients presenting clinical features of Primrose syndrome (Cordeddu et al, ) and additional patients with ZBTB20 mutations have been reported to date (Alby et al, ; Casertano et al, ; Cleaver et al, ; Grimsdottir et al, ; Mattioli et al, ; Stellacci et al, ). Thus, ZBTB20 was established as a gene responsible for Primrose syndrome and 3q13.31 deletion syndrome.…”
Section: Introductionmentioning
confidence: 99%